(13x + 39)(x + 2) * * * * * Don't you think it might, instead, be (13x - 39)(x - 2)? Multiply it out, and see!
13x2=26 By Someone?
2x4 - 9x3 + 13x2 - 15x + 9 = 2x4 - 6x3 - 3x3 + 9x2 + 4x2 - 12x - 3x + 9 = 2x3(x - 3) - 3x2(x - 3) + 4x(x - 3) - 3(x - 3) = (x - 3)*(2x3 - 3x2 + 4x - 3) So the quotient is (2x3 - 3x2 + 4x - 3) and the remainder is 0.
x3 + 13x2 + 42x = x(x + 6)(x + 7).
-x2(5x5 + 13)
36x1 13x2 12x3 9x4 6x6
no. it can be simplified into 13x2. 13 and 2 are prime.
the answer is 13x2=26 posted by a genius
x3+13x2=-22xadd 22x to both sides:x3+13x2+22x=0now factor:x(x2+13x+22)=0x(x+11)(x+2)=0x=0x+11=0x+2=0Therefore the solution to this equation is x=0, x=-11, x=-2
x(x + 5)(x + 8)
It is: (x2 + 5x) (x + 8)
x(x + 8)(x + 5)
4x4 + 13x2 + 36 is a quadratic in x2. The discriminant is 132 - 4*4*36 = -407. Since the discriminant is negative, the expression has no real roots and so it cannot be factorised (in the normal sense of the term).
x3 + 13x2 + 42x = x(x2 + 13x + 42) = x(x2 + 6x + 7x + 42) = x[x(x + 6) + 7(x + 6)] = x(x + 7)(x + 6)
(x - 2)(x + 2)(x - 3)(x + 3)
No because 13x2=26 and they're both prime
5x2 + 3x + 8x2 = 13x2 + 3x = x(13x + 3)
No. If I said 13x2, that would be 26. Then +5 equals 31, so no.